Comparative analysis of genetic polymorphism in Rhaponticum carthamoides (Asteraceae) populations by ISSR markers in the Altai Republic - E. V. Zhmud; I. N. Kuban; A. A. Achimova; M. B. Yamtyrov; O. V. Dorogina (Труды по прикладной ботанике, генетике и селекции)
Background. Rhaponticum carthamoides (Willd.) Iljin (Asteraceae) is a rare species for the Altai Republic (AR).  The purpose of this study was to characterize the genetic polymorphism of Rhaponticum carthamoides at the inter- and intrapopulation level in a comparative analysis for subsequent selection of seed samples from the genetically most heterogeneous natural populations of the AR for practical purposes.   Materials and methods. The species was studied for ISSR variability in five habitats in the AR. DNA from dried leaves of R. carthamoides was isolated using the STAB method. For testing seventeen ISSR primers were used, seven of which were selected as most informative ones.   Results and conclusion. The analysis showed that individual plants from five cenopopulations (CP) were distributed into three groups of similarity on the dendrogram. A separate clade was formed by plant samples from two CPs of the Katun Nature Reserve (KNR). Samples of one of those CPs grew on well-warmed southern slopes and exhibited a higher genetic heterogeneity than the others. The highest intrapopulation and interpopulation similarity in the distribution of DNA fragments was also found in two CPs from habitats with the smallest geographic distance from each other. Representatives of a separate population, least in size and number of individuals in the KNR, showed a high level of similarity in the distribution of DNA fragments. Significantly lower coefficients of genetic similarity with other CPs were found in plants from a small isolated CP from the Shavlinsky Protected Area. It can be assumed that one of the main reasons for the least genetic similarity of this population with others is its location in the immediate vicinity of the foothill at the pass to Achik (Ongudaysky District; absolute height: 2300 masl). This location can be a limiting factor for the exchange of genetic information with individuals from other populations.